Business Strategy in Management Perspective: A Literature Review - Wibowo, Faaizal Ari; Andriani, Nurita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Business development in the world has entered the era of free markets and broad competition, not only in small areas but also in large areas. Efforts made by a company to win the market are by providing competitive advantages, analyzing competitors, and implementing effective and efficient marketing strategies